Combination of brentuximab‐vedotin and ifosfamide, carboplatin, etoposide in relapsed/refractory peripheral T‐cell lymphoma. (22nd December 2020) - Van de Wyngaert, Zoé; Coppo, Paul; Cervera, Pascale; Fabiani, Bettina; Lemonnier, Marie‐Paule; Corre, Elise; Marjanovic, Zora; Aoudjhane, Malek; Mohty, Mohamad; Duléry, Rémy
Abstract: Objectives: Relapsed/refractory peripheral T‐cell lymphomas (PTCL) have a poor prognosis. We aimed at assessing efficacy of ifosfamide, carboplatin, etoposide (ICE) regimen, a known therapeutic option, to which we added brentuximab‐vedotin (BV). Methods: In this study, we retrospectively analyzed patients with PTCL treated with BV‐ICE in our center between July 2014 and March 2018. Results: Fourteen patients received BV‐ICE. Median age was 62 years (range, 31‐73). Main histological subtypes were PTCL‐not otherwise specified (29%), angioimmunoblastic T‐cell lymphoma (21%), follicular‐T helper (21%), or anaplastic large‐cell (15%) lymphomas, all were CD30 positive. Overall response was seen in four (29%) patients, and complete response (CR) in two (14%). Most frequent adverse events were infections, and cytopenia. 2‐year progression‐free and overall survival were 14% and 17.5%, respectively. Conclusion: Patients with relapsed/refractory PTCL treated with BV‐ICE can achieve CR, but few had a sustained response. This association should preferably be used as a bridge to stem cell transplant or be followed by maintenance therapy.